Improving education capacity through home-based worksheet training - Septiyati Purwandari; Aulia Anggi Prastiwi; Sari Nur Arfah; Fatma Hidayah (Community Empowerment, 2022)
Learning media is one of the important instruments in learning activities. The use of media can make it easier for teachers to carry out learning and facilitate students in the learning process. Learning media has many variants, one of which is a module. The learning process carried out at SD Muhammadiyah 1 Muntilan has never used a module as a learning medium. This community service aims to provide training for teachers of SD Muhammadiyah 1 Muntilan in making modules with worksheets. At the end of this activity, the teachers had succeeded in making modules and used them in the learning process. 95% of students feel a positive difference in the learning process after using the module.